High Performance Liquid Chromatography Analysis and Description of Purine Content of Diets Suitable for Dogs with Leishmania Infection during Allopurinol Treatment—A Pilot Trial - Melanie Kaempfle; Michèle Bergmann; Petra Koelle; Katrin Hartmann (Animals, 2023)
Reducing the alimentary purine intake contributes to the prevention of purine (especially xanthine) urolith formation, a common adverse effect of allopurinol treatment in dogs with Leishmania infections. Analyses of the purine content are not required in order to advertise a diet as low in purine. Due to different analytical methods, data provided on purine content are barely comparable. The aim of this study was to investigate the total purine content of 12 different dog diets. For this, the purine bases adenine, guanine, xanthine, and hypoxanthine were determined by standardised high performance liquid chromatography in commercially available urinary diets (n = 4), kidney diets (n = 2), low protein diets (n = 3), 1 vegan diet, 1 regular diet for healthy adult dogs, and 1 homemade low purine diet. Total purine amounts ranged between 10.2 and 90.9 mg/100 g of dry matter. The daily purine intake calculated for a 20 kg standard dog with the analysed diets ranged between 21.9 and 174.7 mg. The lowest daily purine intakes were achieved by 2 urinary urate diets, followed by the homemade diet. Differences in the purine content of commercially available diets need to be considered. Awareness has to be raised when selecting diets for dogs with Leishmania infections during allopurinol treatment in order to minimise the risk of urolith formation.